Analytical appraisal of importance of different fitting parameters in device compact models. Issue 11 (1st May 2014) - Camps, O.; Picos, R.; Roca, M.; Isern, E.; Font, J.; Cerdeira, A.; Estrada, M.; Garcia‐Moreno, E.
Abstract : The main objective of compact device modelling is to perform the best possible fitting of the model to the measured characteristics. To do so, there are some parameters in the models that must be adjusted to the actual values used in the technology, plus some other parameters that are used to overcome some of the limitations of the assumptions used in the model development. Obtaining the first set is usually straightforward, whereas determining the second set is more difficult, because the extraction methods are not always efficient and, moreover, there are parameters that are correlated with others, complicating the whole issue. Moreover, there may be parameters that are not relevant for the specific technology. If one could be able to determine the importance of different parameters, then effort could be better directed by dedicating more effort to the most important parameters. A method to order a list of given model parameters using the calculated importance as the criterion is proposed. This importance is calculated using a modification of the Google PageRank algorithm.